How Tourism Affects Women's Employment in Asian Countries: An Application of GMM and Quantile Regression - Raihan, Asif; Voumik, Liton Chandra; Nafi, Shohel Md.; Kuri, Bapon Chandra (Journal of Social Sciences and Management Studies, 2022)
Based on data collected from 32 Asian countries between the years 1996 and 2020, this study investigated the effect that tourism has on women's participation in the workforce. This research makes use of a panel data model, one-step difference and system GMMs, and quantile regression. Trade, child mortality, FDI, and government spending are all taken into account in addition to GDP. The findings demonstrate that an increase in tourism led to a greater level of female participation in the employment sector. Additionally, exports and FDI both contributed to a rise in the number of women in the labor force. However, both remittances and government spending reduce women's participation in the labor force. Out of the three subsectors, the increase in tourism led to more women working in the industry and service sectors. However, a rise in tourism tends to lead to a decline in the number of agricultural jobs held by women. Women's employment opportunities in the industrial and service sectors grow as a result of tourism but shrink in the agricultural sectors. To analyze labor dynamics, this study is crucial for policymakers. It's useful for promoting tourism in Asia and formulating policy related to it. Employment-related policies in the agricultural, industrial, and service sectors of Asian economies would also benefit greatly from this.